The alcoholic empire : vodka & politics in late Imperial Russia - Herlihy, Patricia (Oxford University Press, 2003)
This text examines the prevalance of alcohol in Russian social, economic, religious, and political life. The author looks at how the state, the church, the military, doctors, lay societies, and the czar all tried to battle the problem of overconsumption of alcohol in the late imperial period. Since vodka produced essential government revenue and was a backbone of the state economy, many who fought for a sober Russia believed that the only way to save the country was through Revolutionary change.; The book traces temperance activity and politics side-by-side with the end of the Tsarist regime, while showing how the problem of alcoholism continued to pervade Soviet and post-Soviet society. Illustrated by timeless and incisive sayings about the Russian love of vodka and by poster art and paintings, this book should appeal to Russian and European historians and those interested in temperance history.